2018
DOI: 10.1007/s11187-018-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Habitual entrepreneurs in the making: how labour market rigidity and employment affects entrepreneurial re-entry

Abstract: We investigate the impact of country-level labour market regulations on the re-entry decision of experienced entrepreneurs, whereby they become habitual entrepreneurs. Multilevel logit models on entry decisions among 15,709 individuals in 29 European countries show that labour market regulations have a positive influence on the decision to re-enter into entrepreneurship. This positive impact is stronger among individuals holding wage jobs at the time of re-entry compared to those that do not. Our results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 75 publications
0
32
0
Order By: Relevance
“…The employees are therefore Bprotected^out of a job and perhaps miss out on career opportunities they would have gladly explored. Fu et al (2018) confirm that strict labor market regulations reduce the mobility between entrepreneurship and employment, although their focus is on habitual entrepreneurs. They show that stringent employment protection makes habitual entrepreneurs more likely to return to entrepreneurial venturing.…”
Section: Dilli and Westerhuismentioning
confidence: 85%
See 2 more Smart Citations
“…The employees are therefore Bprotected^out of a job and perhaps miss out on career opportunities they would have gladly explored. Fu et al (2018) confirm that strict labor market regulations reduce the mobility between entrepreneurship and employment, although their focus is on habitual entrepreneurs. They show that stringent employment protection makes habitual entrepreneurs more likely to return to entrepreneurial venturing.…”
Section: Dilli and Westerhuismentioning
confidence: 85%
“…Evidence to support the hypothesis that strict employment protection limits the mobility of people and thereby inhibits the flow of talent to entrepreneurial ventures would support policies and reforms in that direction. Some of that evidence is found in the paper by Fu et al (2018). This paper takes a nuanced approach and investigates the impact of strict labor protection on the re-entry of experienced entrepreneurs from paid employment and unemployment, respectively.…”
Section: Labormentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to the perception of economic factors by the respondents as a mixed motivation, not strictly negative -the need to set up a business due to a lack of an alternative way to earn money. Fu et al [69] point to an important issue related to re-starting a business which are labour market regulations. They showed that in the case of high thresholds for obtaining paid employment in labour markets with rigid regulations, there is also a high percentage of people entering business again, driven by necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent large-scale studies provide evidence in favor of this theory by showing that in US states that have non-compete covenants to disincentivice skilled personnel to change employers, patenting behavior is more rare (Marx 2011;Marx et al 2015). European evidence also indicates that in national states with higher labor market regulations, innovative entrepreneurship tends to be less prevalent (Fu and Larsson 2018).…”
Section: Explaining the Prevalence Of Innovation Support Policiesmentioning
confidence: 99%